2017
DOI: 10.1016/j.drugalcdep.2017.05.032
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the UPPS-P impulsive personality traits and substance use psychotherapy outcomes: A meta -analysis

Abstract: Background Although impulsive personality traits have been well implicated in substance use disorder (SUD) risk, little work has established how specific impulsive personality traits influence and are influenced by SUD psychotherapy outcomes. The purpose of this meta-analysis was to quantitatively review existing work to examine 1) how impulsive personality traits affect SUD psychotherapy outcomes and 2) reductions in impulsive personality traits during SUD psychotherapy. Methods Studies were identified by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 60 publications
9
86
0
Order By: Relevance
“…In the present study, the magnitude of change in negative urgency was comparable to decreases reported in several previous studies in substance abusing samples [23, 26], providing more evidence that individuals assessed during the course of treatment report decreases in negative urgency. Together with the results of these previous studies, mounting evidence suggests there is some degree of change in how people rate their level of urgency while receiving clinical interventions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the magnitude of change in negative urgency was comparable to decreases reported in several previous studies in substance abusing samples [23, 26], providing more evidence that individuals assessed during the course of treatment report decreases in negative urgency. Together with the results of these previous studies, mounting evidence suggests there is some degree of change in how people rate their level of urgency while receiving clinical interventions.…”
Section: Discussionsupporting
confidence: 89%
“…In one study of patients with binge eating disorder, higher levels of Negative Urgency at the beginning of treatment was associated with worse clinical outcomes and a slower response to treatment over the course of acceptance-based group psychotherapy [22]. Somewhat more is known about how urgency affects the course of treatment for substance use disorders: a small meta-analysis of four studies found that among individuals receiving psychotherapy for substance use disorders, higher levels of Negative Urgency were associated with worse treatment outcomes [23]. Outside of substance use and binge eating disorder, no studies have evaluated how urgency relates to treatment outcomes for psychiatric disorders more broadly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, impulsivity, cortical thickness, and past-month risky behaviors were assessed cross-sectionally, which limits our ability to make strong inferences about the causal relationships between these variables. However, our models are consistent with theoretical models that suggest that trait-level personality factors are relatively stable across the lifespan and, thus, drive engagement in risky behaviors [64,65]. Furthermore, cortical thickness is a relatively stable, and therefore trait-like, neurobiological indicator, which increases the likelihood that it predicts past month risky behavior (rather than recent behavior impacting thickness).…”
Section: Discussionsupporting
confidence: 85%
“…Impulsivity is causally linked to heavier alcohol use (Gullo et al, 2017) and predictive of the development of alcohol misuse (George, Connor, Gullo, & Young, 2010;Moffitt et al, 2011). It is related to poorer SUD treatment outcomes (Charney et al, 2010;Hershberger, Um, & Cyders, 2017a;Loree et al, 2015;Rupp et al, 2016) and associated with enhanced relapse risk 12-months posttreatment (Evren et al, 2012;Müller et al, 2008). As impulsivity is widely considered a stable trait, the goal of intervention is to improve management and expression of impulsivity (Butz & Austin, 1993).…”
Section: Introductionmentioning
confidence: 99%